2022
DOI: 10.3389/fmicb.2021.741391
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Properties of Bifidobacterium longum KABP042 and Pediococcus pentosaceus KABP041 Show Potential to Counteract Functional Gastrointestinal Disorders in an Observational Pilot Trial in Infants

Abstract: Functional gastrointestinal disorders (FGIDs) are a common concern during the first year of life. Recognized as gut-brain axis disorders by Rome IV criteria, FGIDs etiology is linked to altered gut-brain interaction, intestinal physiology, and microbiota. In this regard, probiotics have emerged as a promising therapy for infant FGIDs. In this study, we have investigated the probiotic potential of the strains Bifidobacterium longum KABP042 and Pediococcus pentosaceus KABP041—isolated from healthy children’s fec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…longum is a typical inhabitant of the intestinal tract of breast-fed infants. Speci cally, the strain KABP042 originated from feces of a breastfed infant and is known to exert bene cial effects in lactating infants with colic 19 . Because B. longum and human milk interact in the infant gut we tested the effect of breast milk (which is known to contain around 4.5 mM Pi 20 ) and speci c milk components on poly-P synthesis in the KAPB042 strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…longum is a typical inhabitant of the intestinal tract of breast-fed infants. Speci cally, the strain KABP042 originated from feces of a breastfed infant and is known to exert bene cial effects in lactating infants with colic 19 . Because B. longum and human milk interact in the infant gut we tested the effect of breast milk (which is known to contain around 4.5 mM Pi 20 ) and speci c milk components on poly-P synthesis in the KAPB042 strain.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we used the poly-P-producer probiotic strain B. longum KABP042 to investigate the effect of environmental Pi and whether poly-P formation is involved in protection against acidic or oxidative challenges. Since KABP042 was isolated from the faeces of a breastfed infant 19 and breast milk contains Pi 20 , the effect of breast milk and milk bioactive compounds including human milk oligosaccharides (HMO) and polyamines on poly-P synthesis was also investigated. Furthermore, the effect of B. longum KABP042-derived poly-P in the human intestinal barrier was assessed in vitro by measuring barrier permeability and resistance and the induction of protective factors involved in barrier integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the combination of B. longum and P. pentosaceus has been clinically proven to be effective in the treatment of infantile colic, few studies have investigated the corresponding mechanisms of action in the intestine. Astó et al ( 9 ) conducted in vitro experiments on the potential mechanism of B. longum and P. pentosaceus in the treatment of infantile colic, finding that both strains could tolerate gastric acid, bile salt, as well as other environmental conditions, and could effectively adhere to human intestinal epithelial cells, while synergistically regulating the expression of tight junction-related genes. Notably, these characteristics are crucial for maintaining the integrity of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the probiotic use continued, time and frequency of crying continued to decrease, in addition to significant improvements in the stool properties of infants. Erola et al ( 9 ) similarly demonstrated in their research that the two-strain probiotic combination had a synergistic effect in increasing the diversity of intestinal adhesion proteins during the treatment of infantile colic, in addition to validating its safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, some strains of L. mucosae were found to be resistant to tetracycline, gentamicin, vancomycin, streptomycin, clindamycin, and erythromycin [11,23,29]. B. longum KABP042, isolated from the feces of healthy children, showed resistance to erythromycin and clindamycin [46]. Furthermore, Shin et al [47] reported that many commercial probiotic strains exhibit resistance to various clinically relevant antibiotics.…”
Section: Antibiotic Susceptibility Of the Probiotic Strainsmentioning
confidence: 99%